Evaluating concurrent validity using correlation coefficient for selected physical abilities - Al-Dhaher, Shihab Ahmed Hasan Al-Dhaher; Korkis, Samer Youkhna (Universitas Tanjungpura, 2026)
Background Validity is a fundamental concept in test development and evaluation, ensuring that a test measures what it is designed to measure. One type of validity is concurrent validity, a subtype of norm-related validity, which assesses how closely a new test relates to an established standard being administered at the same time. Objectives This research aims to explore the standard theory of concurrent validity as one type of criterion-related validity, which relies on the correlation coefficient as a means of evaluating the validity of tests for certain physical abilities (balance, agility, coordination). Methods The descriptive-analytical method was used to achieve the objectives of the research. The study sample consisted of 310 students from the Institute of Sports in Duhok Governorate. Personal interviews and content analysis were employed as tools for data collection. Statistical methods used included the arithmetic mean, standard deviation, skewness coefficient, and simple correlation coefficient to derive the research findings. Results The results show that the AMs for the two explosive strength tests were 1.714 and 24.23, with SDs of 5.259 and 6.123. In contrast, the AMs for the speed tests were 3.128 and 4.965, with SDs of 0.342 and 0.672. The values of the correlation coefficient (concurrent validity) for physical ability tests for the age groups (16–17) and (20–21) in the explosive power tests were 0.774 and 0.067, respectively. Conclusion One of the most important conclusions reached by the researchers is that concurrent validity based on the correlation coefficient, as a statistical method, does not provide a comprehensive picture of test validity in the motor domain. This study contributes to the research field by highlighting the limitations of this statistical method in motor domain tests. It emphasizes the need to expand research and develop a comprehensive, multidimensional, performance-based approach to evaluating concurrent validity.